2016
DOI: 10.1371/journal.pone.0159962
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Eating Habits and Physical Activity among Spanish Adolescents. The "Cooking and Active Leisure" TAS Program

Abstract: Worldwide obesity has more than doubled in the last forty years. Even more worrying is the fact that the number of overweight and obese children and adolescents has considerably increased. Socioeconomic development, as well as educational, agricultural and marketing policies have significantly changed dietary and physical activity habits among the youngest, who are thus susceptible to develop chronic and disabling diseases such as diabetes, some cancers and cardiovascular disorders. Adolescence is a critical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 58 publications
(65 reference statements)
1
24
1
2
Order By: Relevance
“…Poor health behaviors and habits, such as poor nutrition and, consequently, obesity [ 5 , 6 ], physical activity, and sedentary behavior [ 7 ], seem likely to persist into a person’s adulthood. Thus, while healthy lifestyle behaviors are essential in all periods of life, the adoption of correct habits and attitudes is preferable during youth and adolescence [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Poor health behaviors and habits, such as poor nutrition and, consequently, obesity [ 5 , 6 ], physical activity, and sedentary behavior [ 7 ], seem likely to persist into a person’s adulthood. Thus, while healthy lifestyle behaviors are essential in all periods of life, the adoption of correct habits and attitudes is preferable during youth and adolescence [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Erhart et al [9] reported that the mechanism of the association between hyperactivity and inattention component and body mass is unknown, and indicated further studies are necessary to obtain a better understanding of the problem [9]. The main factors in excessive body mass are improper eating behaviors and low physical activity [12], but for the hyperactive individuals, there are some doubts associated with the role of indicated factors, especially for the physical activity. It is stated that the association is probably complex, as children and adolescents with hyperactivity are supposed to have a higher level of physical activity than others, but at the same time, the ADHD phenotype is associated with some typical behaviors which include a lower level of physical activity [9].…”
Section: Introductionmentioning
confidence: 99%
“…They became more active after they felt fat, felt that their body weight had increased and felt unwell. This may be explained why the adolescents with higher BMI were found to be more physically active than their low BMI counterparts in several local cross-sectional studies (Zalilah et al, 2006;Rezali et al, 2012), even though other studies showed contradicting outcomes (Roura et al, 2016) or no association between physical activity with BMI (Pon et al, 2004;Woon et al, 2015). Adolescents' choice to be more active in order to control their body weight was demonstrated in a previous study (Lampard et al, 2016).…”
Section: Discussionmentioning
confidence: 96%